Neuromedin U signaling regulates retrieval of learned salt avoidance in a C. elegans gustatory circuit - Jan Watteyne (Nature Portfolio, 2020)
Learning and memory are regulated by neuropeptides. Here, the authors show that the neuropeptide CAPA-1 and its receptor NMUR-1 are required to retrieve learned salt avoidance in C. elegans. CAPA-1/NMUR-1 activation in AFD sensory neurons modulates locomotor programs to express learned avoidance.